Essential role of germ cell glycerol-3-phosphate phosphatase for sperm health, oxidative stress control and male fertility in mice - Abel Oppong; Yat Hei Leung; Anindya Ghosh; Marie-Line Peyot; Marilène Paquet; Carlos Morales; Hugh J. Clarke; Fahd Al-Mulla; Alexandre Boyer; S. R. Murthy Madiraju; Derek Boerboom; Cristian O'Flaherty; et al. (Elsevier, 2024)
Objectives: Obesity, diabetes and high-calorie diets are associated with defective sperm function and lowered male fertility. Mature spermatozoa primarily use fructose and glucose, and glucose and glycerol metabolism are important for sperm function. We recently discovered a novel mammalian enzyme, glycerol-3-phosphate (Gro3P) phosphatase (G3PP), and showed that it operates the glycerol shunt by hydrolyzing Gro3P to glycerol, and regulates glucose, lipid and energy metabolism in pancreatic β-cells and liver. We now observed that G3PP expression is the highest in the testis and spermatozoa, and investigated its role in male fertility. Methods: We examined G3PP expression during spermatogenesis in mouse and assessed male fertility and spermatozoon function in conditional germ cell specific G3PP-KO (cG3PP-KO) mice and tamoxifen-inducible conditional germ cell G3PP-KO (icG3PP-KO) mice. We also determined the structural and metabolic parameters and oxidative stress in the spermatozoa from icG3PP-KO and control mice. Results: G3PP expression in mouse spermatocytes and spermatids markedly increases during spermatogenesis. Male cG3PP-KO mice, in which germ cell G3PP is deleted from embryonic stage, are infertile due to dysfunctional sperm with reduced motility and capacitation, and elevated spontaneous acrosomal reaction and oxidative stress. However, icG3PP-KO male mice do not have altered fertility, due to the presence of ∼10% normal spermatozoa. icG3PP-KO spermatozoa display significantly reduced functionality and morphological and ultrastructural alterations. The icG3PP-KO spermatozoa show reduced glycerol production, elevated levels of Gro3P and reactive oxygen species (ROS), and oxidative stress that is associated with increased mitochondrial membrane potential. Conclusions: Germ cell G3PP deletion leads to the generation of spermatozoa that are functionally and structurally abnormal, likely due to the build-up of Gro3P that increases mitochondrial membrane potential, ROS, and oxidative stress and alters spermatozoa function. Overall, the results indicate that G3PP and the glycerol shunt are essential for normal spermatozoa function and male fertility.